Telenutrition Support in Rare Diseases May Have Positive Effects: Spinal Muscular Atrophy Type 2 Case Report - MUSLU, Mücahit (Duzce Medical Journal, 2023)
In this case report, the 6-month telenutrition counseling process of a 13-year-old male patient diagnosed with spinal muscular atrophy type 2 was discussed. Severe malnutrition was observed in the patient, who used a wheelchair and was fed orally. As a result of examining all the findings, a 6-month telenutrition counseling process was started with a diet containing 50 kcal/kg of energy and 1.85 g/kg of protein per day. At the end of the process, the patient’s body weight increased from 30.5 kg to 35 kg, the body mass index increased from 13.6 kg/m2 to 15.6 kg/m2, and the body mass index Z-score value for age increased from -3.04 to -1.75. The family expressed satisfaction with the counseling process. Patients diagnosed with spinal muscular atrophy require medical nutritional therapy counseling. Telenutrition counseling is considered beneficial in reaching patients and ensuring the treatment process.
Keywords: Medicine (General); Rare diseases; Spinal muscular atrophy; Nutrition; Telenutrition; Infant and Child Health; R; rare diseases; spinal muskuler atrofi; Bebek ve Çocuk Sağlığı; Çocuk Sağlığı ve Hastalıkları (Diğer); Paediatrics (Other); nutrition; R5-920; telenutrition; Medicine; Nadir hastalıklar; Spinal muskuler atrofi; Beslenme; Telenütrisyon; nadir hastalıklar; beslenme; telenütrisyon; spinal muscular atrophy; 2. Zero hunger; 3. Good health